1999
DOI: 10.1046/j.1440-1703.1999.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of land mosaics affecting butterfly assemblage at Mt Ikoma, Osaka, Japan

Abstract: We studied the effects of habitat mosaics on butterfly assemblage on multiple spatial scales: landscape, landscape element, local habitat, and microhabitat, based on the transect counts conducted along a 3.84 km route. The transect route, including 21 local habitats, passed through two distinct areas: 1.65 km of a secondary deciduous Quercus forest and the grove of a shrine in Hiraoka, and 2.19 km of a mosaic of secondary deciduous Quercus forest, grassland, and farmland in Narukawa. The diversity of the lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Moreover, forest interior species are usually conspicuous because they fly when human approach. Canopy species (hairstreaks) and forest interior species (bamboo grass feeders) sometimes become abundant in the forest-dominant areas (Ishii et al 1995;Natuhara et al 1999). Accordingly, excluding fritillaries, we believe that the bias of the counts across species would not be so large, and that our result of relative abundance of each species would reflect the rough characteristics of this area.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, forest interior species are usually conspicuous because they fly when human approach. Canopy species (hairstreaks) and forest interior species (bamboo grass feeders) sometimes become abundant in the forest-dominant areas (Ishii et al 1995;Natuhara et al 1999). Accordingly, excluding fritillaries, we believe that the bias of the counts across species would not be so large, and that our result of relative abundance of each species would reflect the rough characteristics of this area.…”
Section: Discussionmentioning
confidence: 83%
“…Natuhara et al (1999) compared butterfly diversity in two satoyama landscapes, i.e., the heterogeneous landscape with the same proportion of secondary forests and openlands vs. the simple landscape dominated by secondary forests, and reported that the former had more butterfly species despite loss of some univoltine tree-feeding species. However, as vegetation association of each butterfly species in satoyama have not been analyzed, the relative contribution of each vegetation type to butterfly diversity has been unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have suggested that landscape heterogeneity is important for butterfly diversity and species composition (Weibull et al 2000;Hamer et al 2003). Natuhara et al (1999) showed that a landscape mosaic of secondary Quercus forest, grassland and farmland enhanced the species richness of butterflies. Our study site encompassed managed grasslands including different treatments and Abandoned grasslands of various ages within a semi-natural grassland, creating a mosaic of different vegetation in various seral stages, which supports successive flowering through the growing season.…”
Section: Relationship Between the Number And Species Of Butterflies Amentioning
confidence: 98%
“…In contrasts, their absence may reflect declining health (Larson and Collins, 1998). The influence of landscape patterns on butterfly communities have been documented by different authors (Schneider et al, 2003., Natuhara et al, 1999. Sparks and Carey (1995) observed an influence of the floral composition on butterfly diversity.…”
Section: Introductionmentioning
confidence: 93%